Realising 'dialogic intentions' when working with a microblogging tool in secondary school classrooms. (March 2020) - Warwick, Paul; Cook, Victoria; Vrikki, Maria; Major, Louis; Rasmussen, Ingvill
Abstract: In this paper we argue that joint teacher and student awareness of dialogic intentions (DIs) in lessons can focus and guide students' spoken dialogic interactions in the context of the use of digital technology. We focus on DI as a factor in promoting metacognitive awareness of productive dialogue amongst students, considering how teachers in 'dialogic classrooms' express DIs and how the use of a microblogging tool (Talkwall) can support, enhance or disrupt students' realisation of these intentions. Data consist of 17 lessons with Year 7 students (aged 11–12), taught by six teachers and covering three subject areas: English, science and geography. A systematic model is used for analysis of technology-focused student interactions, revealing how technology affordances and constraints are implicated in the realisation of DI. This paper is significant in examining how the ability to engage in dialogue can be focused through learning intentions, or set of intentions, within lessons. Further, it considers how specific technological affordances are central to the ways in which technology is implicated in the creation of a relational space for intra-action that might support teaching and learning.